2020
DOI: 10.1101/2020.03.15.986497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and functional analysis of long non-coding RNAs in autism spectrum disorders

Abstract: BackgroundGenetic and environmental factors, alone or in combination, contribute to the pathogenesis of autism spectrum disorder (ASD). Although many protein-coding genes have now been identified as disease risk genes for ASD, a detailed illustration of long non-coding RNAs (lncRNAs) associated with ASD remains elusive. In this study, our aim was to identify ASD-related lncRNAs and explore their functions and associated biological pathways in autism. MethodsASD-related lncRNAs were identified based on genomic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…We would like to thank Huang et al (2019) for kindly sharing their genomic variant data, which made our identification and further analysis of ASD-related lncRNAs possible. This manuscript has been released as a pre-print at bioRxiv (Tong et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…We would like to thank Huang et al (2019) for kindly sharing their genomic variant data, which made our identification and further analysis of ASD-related lncRNAs possible. This manuscript has been released as a pre-print at bioRxiv (Tong et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Recent studies revealed that many lncRNAs are prevalently expressed in both the developing and adult central nervous systems, especially in the brain [12]. More importantly, accumulating evidence shows that an abnormal lncRNAs expression in neural tissues are closely associated with the initiation and progression of various severe neurological diseases such as glioma, autism, Alzheimer's disease, Parkinson's disease, and schizophrenia [13][14][15][16][17]. Transcriptomic analysis showed that a group of lncRNAs are acutely and dynamically expressed during neuronal activation processes [17].…”
Section: Introductionmentioning
confidence: 99%